Superior Mesenteric Artery occlusion presenting with severe acute abdomen and subsequent gangrenous small gut (Bangladesh Critical Care Journal, 2017)
Superior Mesenteric Artery occlusion is not very uncommon in developing world . It mimic clinically with many differential diagnosis.2 There is a clinical scenario of 60 yrs male, smoker presented in Accident & Emergency (A&E) department with history of central abdominal pain for two days associated with vomiting. Pain was gradually increasing, abdomen became tense, tender and patient developed restlessness. Even after all sorts of conservative management, pain was not subsiding. Following day of admission laparotomy attempted with clinical vision of burst appendix and peritonitis. After exploration of abdomen the finding was thundering. The almost whole small gut was gangrenous , resection anastomosis had done. In this case the differential diagnosis was burst appendix and Intestinal obstruction . Possibility of Superior Mesenteric Artery occlusion should be kept in mind by this clinical ground .Bangladesh Crit Care J September 2017; 5(2): 141-142